The reaction D(e,pp)e 1π- on polarized deuteron at high proton momenta; Few-body problems in physics '98 - Stibunov V. N. Victor Nikolaevich; Loginov A. Yu.; Nikolenko D. M.; Osipov A. V.; Rachek I. A.; Sidorov A. A.; Toporkov D. K. (1999, 1999)
The differential cross section and target asymmetry components of the reaction D(e,pp)e 1π- on polarized deuteron were measured. The kinetic energies of the protons were measured within 55-180 MeV and 46-265 MeV and the acceptance angles in lab. frame are Θ 1,2 = 64° - 82°, Δ ø1,2 = 32°. The sharp peak of the tensor a 20-component of the target asymmetry is found near the invariant mass of the ppπ-system M ppπ = 2300 MeV/c 2. The performed calculations of the differential yield and the tensor target asymmetry do not describe the obtained experimental results